Tool kits for attacks on RSA - Wang, Xu. (2011)
RSA is one of the most popular public-key cryptographic schemes used worldwide. Although the newest standard is semantically secure, it must still be used with care. Many attacks target improper usage of RSA scheme. Hence, this project aims to develop a software toolkit which implements these attacks. It would help its users to verify the security strength of the RSA schemes they are currently using. Three attacks are implemented in this project: Wiener‟s attack on low private exponents; attack on keys with close prime factors and ; and attack on keys with common modulus . All three attacks exploit the weaknesses in RSA key generation process. After experimental analysis, it is found that the effectiveness of these attacks against supplied RSA keys is relatively low.